Corrosion of painted galvanneal steel - Seré, Pablo Ricardo (2015)
The annealing galvanized steel (Galvanneal) is produced from hot-dip galvanized steel thermally treated. The result is a coatingformed by Fe-Zn phases. Its main advantage over the conventional galvanized steel is the absence of the characteristic spanglesaffecting these coatings and the presence of iron providing better weldability than the pure zinc coating. In this work, thecorrosion behavior of pre-treated and painted with environmentally friendly schemes, conventionally hot-dip galvanized, andannealing galvanized (Galvanneal) steel were studied. A g-mercaptopropyltrimethoxysilane (MTMO) pre-treatment was applied.A waterborne polyurethane paint developed at CIDEPINT was used. Assays were performed in the salt spray and controlled humidity chambers. The metal-paint adhesion was determined by Tape Test. The systems deterioration was evaluated by means of periodical visual inspections, optic and electron microscopes, EDXS, and electrochemical impedance measurements. The MTMO showed to be a good adhesion promoter for the systems exposed to the present testing conditions.